Factors Influencing Generation Z Intention in Using FinTech Digital Payment Services - Andrew Christian Aseng (Fakultas Ilmu Komputer, Universitas Klabat, 2020)
Many studies related to financial technology (FinTech), especially digital payment services, have been carried out. However, there is still a lack of studies that focus on Generation Z, especially their intention to use the service, while this generation is very familiar and is easily adaptable to new technologies. In addition, it is projected that this generation will contribute greatly to online transactions in Indonesia and even the world. For this reason, this study focuses on factors that can influence Generation Z’s intention to use digital payment services. There are five independent factors that will be tested, namely: culture, perceived security, performance expectancy, effort expectancy, and social influence. The research instrument was a questionnaire adopted from related literature, which was distributed online using the snowball and convenient sampling method. A total of 266 Generation Z people participated in this study. A descriptive statistic and multiple regression analysis were performed and found that simultaneously these five factors had a significant positive effect (Sig <.05) on the intention of Generation Z in using the service. This study concludes that service providers have to pay attention to these factors in attracting Generation Z.Keywords—digital payment services, financial technology, Generation Z